For A Man or A Woman? Gender Determination from Various Foramina and Canals of Maxilla on Cone Beam Computed Tomography (Cbct): A Retrospective Radiographic Study - Patel, Twinkal; Dudhia, Bhavin; Jani, Yesha; Shah, Deep; modi, Siddharth; shah, Dhruvi (Journal of Neonatal Surgery, 2025)
Introduction: Identification of corpses is a complex forensic procedure mandated by legal and social frameworks. Forensic dentistry and anthropology focus on addressing challenges in sex determination; often relying on morphological features of the maxilla, particularly foramina and canals. Conventional 2D imaging modalities face limitations, prompting exploration of advanced technologies like cone beam computed tomography (CBCT) to enhance accuracy. Aim: This study aims to contribute to forensic medicine by evaluating maxillary foramina and canals using CBCT for improved gender determination. Materials and Methods: A dataset of 200 CBCT scans from the Oral Medicine and Radiology department was analyzed, adhering to strict inclusion and exclusion criteria. Measurements of foramina and canals were conducted, and statistical analysis was performed using SPSS software. Results: This study reveals gender-based differences in the incisive canal and foramen dimensions, emphasizing the need for gender-specific considerations in anatomical research and clinical applications. Similarly, significant variations in the greater palatine canal and foramen measurements, excluding location characteristics, are found. Conclusion: The research advocates for the integration of advanced imaging techniques to enhance precision in forensic investigations. This forensic odontology study underscores the evolving landscape of gender determination using CBCT.